Psychological aspects of start situation of sportsman/ sportswoman - Graczyk, Marek; Pęczak, Alicja; Wójtowicz, Stanisław (Studia Psychologica: Theoria et praxis, 2004)
^pDuring the proceedings of the XXXI Conference of the Polish Psychological Society a body of competent judges recognized the psychological condition at the moment of start in sport to be a life threatening one and ranked together with such situations as natural disasters, military operations or acts of terror. Competing in some sports such as martial arts and auto and motor racing involves even a risk of death. The stress of competition itself can be viewed as one approximating situations of natural disasters or combat situations. In addition, an injured athlete faces self-doubts regarding their health, fitness levels, and athletic ability (Cogan & Vidmar, 2000; Morris & Summerf, 1998). Consequently, two types of pre-competitive phobia might be developed (PPA, 2002): hyper-mobilization (or over-activation) and hypo-mobilization (or apathy). This presentation will describe a theoretical background useful in working with injured athletes. Next, a discussion will be conducted on how monitoring psychomotor responses has a unique diagnostic and predictive potential in consulting with elite performers in sports. Practical solutions to problems faced in assisting athletes in overcoming injuries will be described including (a) mental training (Unestahl, 1979), (b) cognitive-attributional, motivationalemotional, and psychomotor-behavioral self-regulation (Graczyk & Dworakowska, 1996), (c) ideomotor training (Morris & Summerf, 1998), and (d) optimizing coaching interpersonal styles (Graczyk, 2002). The content of this presentation is based on a line of applied research and the author’s consulting career involving Olympic preparation to Sydney 2000.